An Innovative Technique of Reconstructing Combined Extensor Tendon Zone (z5 and z4) Defect, Utilizing an Adjacent Proximal (z6) Tendon, as a Distally Based Tendon Flip Flap, in the Index Finger - Narendra S. Mashalkar; Pooja Thoppal Shiva; Joseph Kattady (Indian Journal of Plastic Surgery)
Delayed reconstruction of segmental extensor tendon defects of the hand has been described with auto-tendon grafting or by using local flaps harvested from the native tendon. These reconstructive techniques have been described in certain extensor tendon zones, mainly in zones 2, 4, and 5 of the hand. Borrowing auto-tendon grafts will have donor site morbidity. The use of available local tendon as flap may be considered, the tendon harvesting being done from a part of the native tendon from either proximal or distal location. The index and little fingers have the advantage of having two tendons to do the same function and hence these tendons may be utilized as a whole to our advantage as distally based tendon flip flap to reconstruct zone 4 and 5 extensor tendon defects with good functional outcomes.